PRODUCTION OF FUNCTIONAL MALE BROODSTOCK OF CORAL TROUT GROUPER (Plectropomus leopardus) - Sari B. Moria Sembiring; Jhon H. Hutapea; A. Muzaki (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Fertilization rate of the first generation of coral trout grouper, Plectropomus leopardus from wild broodstock in cultured tank was relatively low of 10-35%. Based on gonad histology analysis of 30 samples, only one male was found in early stage maturation. Therefore, it is needed to increase functional male production to ensure an increase level of egg fertilization. The experiment was conducted for 9 months using coral trout broodstock, from wild stock as control and selected F1 from culture as treatment. Broodstocks were reared in three tanks, each was 100 m3 in volume with 54 fishes/tank. All selected cultured fish (F1) in tank C were implanted with 17a-MT hormone at 50 mg/kg of body weight every month for 3 consecutive months. Wild stock fish in tank A and selected cultured fish (F1) in tank B were not implant as controls. The result showed that the number of male  increased 6 times in implanted by 17a-MT hormone compared to fish without implant only increased 2 times. Therefore, eggs fertilization and hatching rate were significantly increased by implanting F1 broodstocks with hormone17a-MT. Keywords: Functional male, broodstock, Coral trout (Plectropomus leopardus)